A pergunta e seus contributos para as estratégias de resolução de problema algébrico no 3º ano do ensino médio - Pinheiro, Joseane Mirtis de Queiroz (2016)
The aim of the present research was to investigate how questions can promote the development of strategies to solve an algebraic problem in the 3rd Grade of High School. It was carried out with students of the 3rd Grade of High School of a Public School from the State Educational System of the city Afogados da Ingazeira - PE, from June/2015 to December/2016. The Methodology uses qualitative research. These are case studies, two case studies were carried out, whose participating students were indicated by the teacher. It was used as data collection instruments the application of semi-structured interviews to the teacher in charge of the class and to the students who were part of the case studies, and the execution of a problem solving task with the students. The results suggest that the teacher in charge values the Problem Solving Methodology and uses exercises, although she thinks that she is using problems. Therefore, the question in her classes seems to be reduced to the IRE standard. Beatriz understands that solving problems is different from doing exercises. For Beatriz, the act of asking functions basically to clear up doubts and remind about previously studied subjects. Actual questions and examination questions allowed us to obtain information and a survey of previous knowledge from the student. The didactic questions, on the other hand, explored her way of thinking about Mathematics, interpretation, search for solutions, reflections and conjectures, besides favoring the written calculations. Beatriz developed basically two solving strategies for the algebraic problem. In the first one she used arithmetic, specifically the operations of addition, subtraction, multiplication and division. In the second she used the System of Linear First Degree Equations. The questions helped her to make decisions and to proceed with the development of the System satisfactorily. For Julia, a problem is a question that brings a challenge that needs to be understood and then solved. Her conception about a question is that it is important to remember subjects previously studied, to clarify and to complete something that you already know or even about content when you do not understand something. The actual questions, the exam questions and the didactic questions made her expose her previous knowledge and provide information about them to the researcher teacher, what helped her in other actions regarding the problem. With the didactic questions, Julia reflected more about what is in the problem, like the information and the graphical representation, which helped her in the reflections to search for solutions. She developed basically two strategies to solve the algebraic problem. In the first one, she used the arithmetic fundamental operations, specifically addition, subtraction and division, without presenting any difficulty. In the second one, she used the Algebra and she elaborated three equations with the weights using the algorithm of Systems of Linear First Degree Equations, without presenting any difficulty. The algebraic language and its representation do not seem to have been a problem for her. The questions made her broaden her algebraic thinking, considering the way how she demonstrates the organization of the problem.